Municipal solid waste - Management cost and opportunities - Kathiravale, Sivapalan; Ahnantakrishnan, Jeyananda Chinniah (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/